Characterization of wood and high-ash biochars and their effects on the fertility of tropical soils - Domingues, Rimena Ramos (2017)
Biochars presents itself as an emerging technology and has demonstrated great use versatility. In addition to being an alternative for the management of agricultural biomass, the addition of biochars can contribute in different ways to the improvement of soil fertility status. Due to the high content of pyrogenic C, the application of biochar in weathered soils is strongly desirable, since these soils present, due to climatic conditions, low levels of organic matter (OM) and, consequently, low capacity to retain nutrient – low CEC. By combining biomass with pyrolysis temperatures, it is possible to obtain a series of charred matrices with properties capable to change soil properties. The aims of this study were: (i) to characterize chemically and physically the biochars produced from five biomasses massively found in Brazil in in different pyrolysis temperatures, (ii) to evaluate the fertility of soils of contrasting texture and organic matter (OM) amended with contrasting biochar samples and incubated during 1 year; (iii) to investigate the effectiveness of biochars in changing soil properties considering the dynamics of soil fertility attributes; (iv) to evaluate the CEC of soils with contrasting textures and OM and treated with increasing rates of wood and high-derived biochars. Fifteen biochars originated from five biomasses (chicken manure, eucalyptus sawdust, coffee husks, sugarcane bagasse and pinus bark) pyrolyzed at three different temperatures (350, 450 and 750 ºC) were characterized by proximate analysis, elemental composition, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), pH, electrical conductivity (EC), CEC, soluble carbon and liming value. The Ca and K content of the biomasses, the high pH and liming value as well as the presence of carbonates in the biochars of coffee husk and chicken manure indicate the potential of these charred matrices to act as liming materials and to supply nutrients (K and P) in tropical acidic soils. Biochars derived from wood and sugarcane have greater potential for improving C storage in tropical soils tha high-nutrient derived biochars due to a higher aromatic character of lignified biochars. In the second experiment, pH, CEC, available P and K and exchangeable Al were determined in Latosol and Neosol treated with coffee bark and pine bark biochars at a rate of 2% (w/w). High-ash biochar, such as coffee husk, reduced the acidity of the soils and increased the availability of K excessively at the beginning and during the one-year basis soil-biochar incubation. The effect of the coffee husk on the availability of P was dependent on the pyrolysis temperature employed during high-nutrient biochars. Biochars from pinus bark, rich in condensed and aromatic C, was not effective in changing the soil fertility status, but was very effective in increased the C stored in soils. Finally, it was investigated the effect of increasing rates twelve biochars (derived from chicken manure, eucalyptus sawdust, coffee husks and sugarcane bagasse and pyrolysed at 350, 450 and 750 ºC) on the changes of CEC of contrasting textural and OM tropical soils. CH and CM biochars are very effective in change soil CEC, but increased in negative charge density is soil-dependent. In fact, increase in soil CEC rely on the biomass, pyrolysis temperature, biochar CEC, changes in soil pH of soil biochar treated soil and also depends on the soil investigated and its interaction with the biochar applied. The positive effects of biochar on soil CEC was predominantly affected by high CEC-biochar and its capacity do neutralize soil acidity, which are positively linked to high-ash biochars produced at low-temperatures (350 ºC).